An analysis of shape and colour preferences in children’s drawings produced during the schematic stages / Nuraini Razman - Razman, Nuraini (Faculty of Education, 2014)
The purpose of this study is to identify shapes and colours preferences that being used in drawing of schematic stage children’s. It also to know the children’s preferences in using of specific colors category and the mastery level of geometry shape based on upon the house, tree and car objects in drawings. Fifty four students from Sekolah Rendah Kebangsaan Seri Jasa Sepakat, Batu Pahat Johor were selected to be participated in this research. The sample has been selected randomly. The Data will collect and analyzed by means of observation methodology and descriptive format. The results will showed that there were differences of using colors preferences in schematic stages children’s on drawing according to genders. There also will having a differences level on use of the geometrical shapes of schematic stage children’s according to genders. This indicates that the schematic stages child’s drawing not wholly determined by realism.